Abnormal resting‐state effective connectivity in reward network among long‐term male smokers. (8th August 2022) - Zhang, Mengzhe; Gao, Xinyu; Yang, Zhengui; Han, Shaoqiang; Zhou, Bingqian; Niu, Xiaoyu; Wang, Weijian; Wei, Yarui; Cheng, Jingliang; Zhang, Yong
Abstract: Background: Tobacco addiction is a chronic, relapsing mental disorder characterized by compulsive tobacco seeking and smoking. Current evidence shows that tobacco addiction exerts their initial reinforcing effects by activating reward circuits in the brain, but the causal connectivity among reward circuits is still unclear. Therefore, it is vital to understand how the reward network works to lead to the compulsive smoking behaviour. Method: We applied dynamic causal modelling (DCM) to resting‐state functional magnetic resonance (rs‐fMRI) to characterize changes in effective connectivity (EC) among eight major hubs from reward network between 76 long‐term male smokers and 55 nonsmoking volunteers (matched with age, gender and education). Results: Relative to the healthy controls, long‐term smokers had stronger ECs from the right anterior insula to left ventral striatum, posterior cingulate cortex (PCC) to ventral tegmental area (VTA), PCC to left anterior insula, left anterior insula to VTA, and ventromedial prefrontal cortex (vmPFC) to PCC and weaker ECs from the VTA to left ventral striatum, right anterior insula to right ventral striatum, and anterior cingulate cortex (ACC) to right anterior insula. Conclusions: Overall, our findings revealed disrupted neural causal interactions among parts of the reward network associated with tobacco addiction, expanding the growing evidence for the potential neurobiological mechanisms of tobacco addiction. We found abnormalities within the mesocorticolimbic system and a top‐down regulation disorder in the dopamine‐dependent process of response inhibition and salience attribution among long‐term smokers, which may facilitate the development of effective therapies in tobacco addiction. Abstract : This study revealed disrupted neural causal interactions among parts of the reward network associated with tobacco addiction. We found abnormalities within the mesocorticolimbic system and a top‐down regulation disorder in the dopamine‐dependent process of response inhibition and salience attribution among long‐term smokers, which may facilitate the development of effective therapies in tobacco addiction.